Influence of Social Media on Sustainable Purchasing Behavior: A Systematic Literature Review - Ramandini, Nabila; Oktawandari, Hargianti Henni; Batu, Kardison Lumban (LifeSciFi, 2025)
The increasing urgency of environmental sustainability, combined with the rapid growth of social media usage, has significantly influenced consumer behavior in the digital era. Social media has evolved beyond a mere communication tool into a powerful space where consumer values, perceptions, and attitudes are shaped. Through mechanisms such as parasocial interactions with influencers, peer influence in online communities, and exposure to trust-based and user-generated content, consumers are increasingly encouraged to adopt sustainable purchasing behaviors. This study aims to examine these dynamics by conducting a systematic literature review focused on the role of social media in shaping consumer attitudes and behavior toward sustainable products. A total of 205 scholarly articles published between 2020 and 2025 were retrieved from the Watase Uake database, and 50 of them were selected for in-depth review based on relevance, quality, and methodological rigor. The selected literature was analyzed to explore patterns and trends related to consumer motivation, behavioral intention, and the effectiveness of social media in promoting sustainable consumption. The findings provide valuable insights into how digital platforms support sustainability goals and influence consumer decision-making. This review also identifies key research gaps and calls for future empirical studies to better understand and optimize the role of social media in encouraging ethical and environmentally conscious consumer practices.